An overview of carbon-carbon composite materials and their applications - Agarwal, Nilesh; Rangamani, Aditya; Bhavsar, Kathan; Virnodkar, Shreyash Santosh; Fernandes, Aldrin Antonio Agostinho; Chadha, Utkarsh; Srivastava, Divyansh; Patterson, Albert E.; Rajasekharan, Vezhavendhan (Frontiers in Materials, 2024)
Carbon-carbon composites are advanced materials known for their high strength, high-temperature stability, and superior thermal conductivity. Mechanical properties such as tensile strength, flexural strength, and compressive strength are examined, as well as thermal properties like the coefficient of thermal expansion and thermal conductivity, to understand the characteristics of the composite. Carbon-carbon composites are ideal for the aerospace industry's need for lightweight and high-performance materials. Tribological and surface properties are relevant to this discussion, given the use case of carbon-carbon composites in extreme conditions, the effect of exposing the composite to different fluids and the change in friction and wear properties. Coatings can protect the composite from environmental factors such as UV radiation, oxidation, and erosion. Self-healing composites that can repair themselves can increase the lifespan of structures while reducing maintenance costs. These have been used in aerospace applications such as airplane braking systems, rocket nozzles, and re-entry vehicle heat shields. Furthermore, researchers have recently addressed the problem of finishing and drilling without delamination and loss of properties, and this study looks into unconventional methods that can be adopted for the same. This study aims to provide an overview of the current state of carbon-carbon composite materials and their applications.